Getuigenis 1936. (Antwerpen : [s.n.], 1936)
"Vlaams, kultureel, links gericht vrijzinnig tijdschrift"
Vaste medewerkers: André Claudet, Jef De Meyer, J. Henner, Jef Last, R. Maudoux, M. Mommens
Periodiciteit: maandelijks
Nederlands
Periodiek
Keywords: cultuur; politiek; antifascisme